Altered resting-state voxel-level whole-brain functional connectivity in depressed Parkinson's disease. (May 2018) - Wang, Hansheng; Chen, Huiyue; Wu, Jiahui; Tao, Li; Pang, Ya; Gu, Min; Lv, Fajin; Luo, Tianyou; Cheng, Oumei; Sheng, Ke; Luo, Jin; Hu, Yida; et al.
Abstract: Background: Depression is one of the most common non-motor symptoms in Parkinson's disease (PD), but its pathogenesis is still not very clear. Recently, degree centrality, a voxel-level whole-brain functional connectivity (FC) analysis of resting-state functional magnetic resonance imaging, has provided the most promising way to explore the neural network mechanisms underlying depressed PD. Methods: Degree centrality, voxel-wise image and clinical symptoms correlation and secondary seed-based FC analyses were performed in twenty-seven drug-naïve, early stage depressed PD patients, 27 non-depressed PD patients and 27 healthy controls (HCs) to reveal voxel-level whole-brain FC changes in depressed PD. Results: Compared with the HCs, depressed PD and non-depressed PD patients shared similar brain degree centrality abnormalities mainly in the basal ganglia, insular cortex, motor cortices, default mode network, prefrontal gyrus and the cerebellum. However, compared with non-depressed PD, depressed PD showed degree centrality abnormalities in the right middle prefrontal gyrus, anterior cingulate cortices, supplementary motor cortices and cerebellum lobule VI. The right middle prefrontal gyrus degree centrality abnormalities were correlated with the clinical depression severity, and using it as a seed, a secondary seed-based FC analysis further revealed the FC changes in the anterior cingulate cortices and the cerebellum lobule VI. Conclusions: Our findings revealed that dysfunction in extensive brain areas were involved in depressed PD, and among these regions, the right middle prefrontal gyrus, anterior cingulate cortices and the cerebellum may pose as pathogenesis hubs underlying depressed PD. Highlights: Depressed PD patients present voxel-level FC abnormalities in motor and non-motor networks. Among these brain areas, the RMPFG, ACC and cerebellum may pose as pathogenesis hubs.